SUN-595 Chronic Diarrhea as a Manifestation of Medullary Thyroid Cancer - Shakir, Mohamed (J Endocr Soc, 2019)
Background: Tumor secretion of calcitonin (Ct), Ct gene-related peptide, or other substances can cause diarrhea in patients with advanced medullary thyroid cancer (MTC). We report 3 patients with chronic diarrhea due to MTC in whom the diagnosis was delayed. Case 1: A 26-year-old man reported to Gastroenterology (GI) clinic with a 6-month history of diarrhea. An extensive work-up was performed including upper and lower endoscopies that were unrevealing. A diagnosis of chronic diarrhea of unknown etiology was made and patient received symptomatic treatment. Six months later the patient lost about 16 pounds of weight; a chest CT was performed showing a left thyroid mass with cervical lymphadenopathy and skeletal metastases. Biopsy of the thyroid mass confirmed MTC. Serum calcitonin (Ct) level was 52894 ng/L (ref <10). Additional tests (serum VIP, somatostatin, glucagon, pancreatic polypeptide, neurotensin, and gastrin levels) were normal. Two months post thyroidectomy and lymph node dissection, Ct level was 447 ng/L and diarrhea improved. Subsequently serum Ct started rising and imaging studies showed extensive metastases and presently patient is treated with tyrosine kinase inhibitors. Case 2: A 27-year-old woman was referred to GI clinic with a 3-month history of diarrhea. Upper endoscopy and colonoscopy were noncontributory. Detailed laboratory evaluations were normal and a diagnosis of irritable bowel syndrome was made. One month later, thyroid nodules were detected and biopsy of the thyroid nodule revealed MTC. Serum Ct was 2890 ng/L. Patient underwent total thyroidectomy and histology confirmed MTC with metastasis. Two months later, serum Ct was 490 ng/L with improvement in diarrhea and reduced loperamide dosage. Case 3: A 38-year-old man was referred to GI clinic with a 4-month history of diarrhea. Patient underwent a detailed evaluation and was treated with loperamide and tincture of opium with partial improvements. Three months later, a physical examination revealed a 4-cm left thyroid nodule and biopsy suggested MTC. Serum Ct level was 4088 ng/L. Patient underwent total thyroidectomy and lymph node dissection. Histology confirmed MTC. Two months postoperatively, serum Ct level normalized and diarrhea completely resolved. Discussion The link between tumor humoral secretion and diarrhea is well established in patients with MTC as diarrhea is more frequent with metastatic disease and immediately improves after resection of the tumor. The improvement in diarrhea was seen in our patients postoperatively. Diarrhea may result from a secretory process induced by elevated circulating Ct or other substances such as prostaglandin or serotonin. Other proposed mechanisms include decreased absorption in the colon secondary to motor disturbances. In conclusion, MTC should be considered when evaluating chronic diarrhea.